Enhanced Dye-Sensitized Solar Cells with Catalytic Carbon Aerogel Counter Electrodes. (20th August 2015) - Chen, Haijun; Liu, Tao; Wang, Ning; Zhao, Lijuan; Zhao, Qinghong; Ren, Jing; He, Hongcai; Lin, Hong
Abstract: Carbon aerogel (CA) with ultra-low density and three dimensional network nanostructures is investigated as the electrocatalyst for tri-iodide (I3 − ) reduction in dye-sensitized solar cells (DSSCs). The catalytic properties of CA and platinum (Pt) counter electrodes are analyzed and compared by electrochemical impedance spectroscopy (EIS) and Tafel polarization measurements. The devices applying CA counter electrode exhibit a lower charge-transfer resistance (1.60 Ω cm 2 ) and larger diffusion coefficient (3.39 × 10 −6  cm 2  s −1 ) compared to the devices with conventional Pt counter electrode. As a new kind of porous carbon materials, CA counter electrode has high active surface area and conductance. These factors improve the power conversion efficiency ( η ) up to 8.04%, which is better than that of the reference Pt based DSSC (6.79%). This paper indicates that carbon aerogel with good catalytic activity can potentially be used as a promising alternative to the expensive Pt counter electrode in a high-performance DSSC device design.